2012
DOI: 10.1007/s10802-012-9696-6
|View full text |Cite
|
Sign up to set email alerts
|

The Strengths and Difficulties Questionnaire (SDQ): the Factor Structure and Scale Validation in U.S. Adolescents

Abstract: The Strengths and Difficulties Questionnaire (SDQ) is one of the most commonly used instruments for screening psychopathology in children and adolescents. This study evaluated the hypothesized five-factor structure of the SDQ and examined its convergent validity against comprehensive clinical diagnostic assessments. Data were derived from the National Comorbidity Survey - Adolescent Supplement (NCS-A), a nationally representative sample of U.S. adolescents aged 13 to 18 years. Parents/parent surrogates (n=6,48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
159
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 54 publications
19
159
0
5
Order By: Relevance
“…The study of the internal structure, by means of CFAs, supported the five-factor structure in all the countries and in the total sample, as it is the case in previous studies [40,27,11,24,28,29,25].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The study of the internal structure, by means of CFAs, supported the five-factor structure in all the countries and in the total sample, as it is the case in previous studies [40,27,11,24,28,29,25].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies, conducted using confirmatory factor analysis, showed the five-factor solution as the most appropriate [27,24,11,28,29,25], while others found the three-factor model [30][31][32]11]. The threefactor solution is composed by Internalizing symptoms, resulting of the Emotional and Peer problems subscales, the Externalizing symptoms, composed by Conduct problems and Hyperactivity subscales, and the Prosocial subscale.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In case of a multidimensional construct, we assume that the scale is split into subscales. For example, the Strengths and Difficulties Questionnaire (SDQ) consists of five subscales (He, Burstein, Schmitz, & Merikangas, 2013). Subsequently, omega is reported per subscale.…”
Section: Factor-analytic Evidencementioning
confidence: 99%
“…(Youthinmind Ltd, 2015) As the participants in this study were adolescents (junior and senior high school students), the SDQ version used in this study was the self-report version. This instrument has been widely used worldwide (Gómez-Beneyto, 2013;He, 2013;Liu, 2013), as well as in Indonesia in the previous study (Ang, 2007).…”
Section: Strength and Difficulties Questionnaire (Sdq)mentioning
confidence: 99%